Soil Moisture Mapping at Paddy Field in Indramayu Residence Using Landsat 8 OLI/TIRS - Mochamad Firman Ghazali; Tri Muji Susantoro; Ketut Wikantika; Agung Budi Harto; Rian Nurtyawan (Bogor Agricultural University, Indonesia, 2020)
Drought monitoring is important for the paddy planting planning. Remote sensing is one tool can be used for it. Paddy field monitoring based on the soil moisture gives much knowledge related to the water content in the soil. Soil moisture analysis in this study is using Normalized Different Water Index (NDWI), Linear Soil Moisture (LSM), and Tasseled Cap. Soil moisture change could explain based on calculation results of NDWI, Linear Soil Moisture (LSM), and Tasseled Cap Transformation (TCT). Based on the results has explained that the driest year occurs in 2015 and June 2016 has a higher soil moisture. Comparison with the radar shows that the results of soil moisture analysis with Landsat was effective can be used with results relatively close to the radar results.